The Development of a Ventilator Counting System Based on the Internet of Things for Hospitals - Choosri, Pranomkorn; Solos, Sirirat; Sareebot, Tawiwan; Sinchoo, Po (PKRU SciTech Journal, 2025)
The research focused on developing a counting system for spare ventilators in the emergency room of a hospital in Bangkok using Internet of Things (IoT) technology. The system aimed to prevent ventilator shortages during emergencies and reduce the workload of staff who would otherwise need to manually check the ventilator count. It was designed to count ventilators using object-detection infrared sensors and transmit the data via Wi-Fi, which was then displayed on a webpage. Hospital staff could continuously monitor the remaining number of ventilators, and a notification system via the Line application alerted them when the number of ventilators dropped below a set threshold. This allowed staff to promptly replenish ventilators as needed. The test results demonstrated that the sensors detected ventilators with 97% accuracy, while the alert system performed with 100% accuracy. For future development, improvements are expected in the aesthetic presentation of the website and the connectivity of devices in areas without wireless internet access.